Strategic assessment of yam research priorities. - Abdoulaye, Tahirou; Alene, Arega D.; Rusike, Joseph; Akinola, Adebayo A. (2014)
This paper documents the procedure and findings of an ex-ante assessment of key yam research options. Following the general methodology agreed for the RTB priority assessment, the economic surplus model was used to estimate benefits for the different scenarios. In the end, five research options were considered for analysis based on available data and methodological suitability. These were (1) improved yam varieties with complementary ICM options, (2) clean planting materials and agronomic practices, (3) postharvest innovations, (4) pest and disease management options, and (5) ICM interventions. Model results show that, under the low adoption scenario, the land area coverable by different technologies ranged 220,000–870,000 ha in all the yam-growing countries.